Leader knowledge hiding, feedback avoidance and hotel employee outcomes: a moderated mediation model. Issue 2 (30th November 2021) - Akhtar, Muhammad Waheed; Karatepe, Osman M.; Syed, Fauzia; Husnain, Mudassir
Abstract : Purpose: The purpose of this paper is to develop and test a research model that investigates feedback avoidance behavior (FAB) as a mediator of the impact of leader knowledge hiding (LKH) behavior on creativity and job performance. The model also examines whether leader-follower value congruence (LFVC) moderates the aforementioned mediating linkages. Design/methodology/approach: Data were collected from hotel managerial employees in two waves and their superiors in Pakistan. The hypotheses were gauged via macro PROCESS. Findings: The findings reveal that LKH behavior intensifies employees' FAB, which, in turn, impedes their creativity and job performance. The findings further demonstrate that the positive impact of LKH behavior on FAB is stronger among employees high on LFVC. Practical implications: Management should arrange workshops that highlight the critical role of leader's knowledge sharing with the relevant individuals. This is so important because knowledge hiding behavior heightens FAB and erodes creativity. These workshops can be followed by training programs, which focus on the importance of knowledge exchange and feedback-seeking behavior. Top managers' and/hotel owners' participation in these programs can be a force for mutual trust and cultivate LFVC. Originality/value: The hospitality and tourism literature is devoid of evidence about the underlying process through which LKH behavior influences employee outcomes. The paper enhances current knowledge by proposing FAB as a mediator of the influence of LKH behavior on creativity and job performance. The paper is the first of its kind by assessing whether LFVC moderates the indirect influence of LKH behavior on creativity and job performance via FAB.